Experimental Study on an Innovative Hollow Concrete Floor System Assembled with Precast Panels and Self-Thermal-Insulation Infills - Liang Gong; Zhongfan Chen; Yan Feng; Sihan Ruan; Liuhui Tu (Advances in Civil Engineering)
This paper presents an innovative hollow concrete floor system comprising hollow precast panels and self-thermal-insulation infills. The precast panels are connected by welded reinforcement bars and cast-in-situ concrete joints. To study the vertical load-carrying capacity and the working mechanism of this innovative floor system, a static loading test was carried out on a 1/2 scale model. The specimen consists of six precast slab members, four precast reinforced concrete beams and columns, respectively. Experimental and simulation results related to the crack development and vertical load-carrying capacity were analyzed. It is found that the innovative floor system could meet the capacity requirements of the Chinese code. Furthermore, the crack development of the innovative system shows similar characteristics with the solid floor. To explore the feasibility of the existed analysis methods, the specimen was simulated and compared by nonlinear analysis in ABAQUS. The comparison illustrates that the analogue cross beam method is more accurate and suitable for the simulation of the innovative hollow concrete floor system.